58.4k views
5 votes
Reminder when performing your check step, always substitute your solution by enclosing it in parentheses. -x + 3 = 2(3 - 2x)

User TheWebs
by
4.4k points

1 Answer

5 votes

Answer:

x = 1

Explanation:

For the equation given, we have to solve for the value of "x".

First, when simplifying, we will need the distributive property shown below:

Distributive Property:

a(b - c) = ab - ac

Now, lets do algebra:


-x + 3 = 2(3 - 2x)\\-x+3=2(3)-2(2x)\\-x+3=6-4x\\-x+4x=6-3\\3x=3\\x=(3)/(3)\\x=1

The value of x is 1

Lets substitute x = 1 into equation to check:

-x + 3 = 2(3-2x)

LEFT SIDE:

-(1) + 3

= -1 + 3

=2

RIGHT SIDE:

2(3-2x)

2(3-2(1))

=2(3-2)

=2(1)

= 2

This is indeed the solution since left hand side equals right hand side

User Kuroi Neko
by
4.6k points